Ameliorative effects of L-carnitine on florfenicol-induced hepatotoxicity in broilers - Haggag, Nourhan A.; Aziz, Mustafa A.; Zahra, Abu Elnasr A.; Belih, Soad S.; Khalifa, Hazim Omar (Journal of the Hellenic Veterinary Medical Society, 2022)
L-carnitine is a non-essential amino acid derivative naturally occurring and widely distributed in nature. It received a growing interest in its potential uses as a medicinal agent possess protective effects that postulated to be related to its antioxidant action. This study was aimed to evaluate the ameliorative role of L-carnitine on florfenicol induced hepatic toxicity in broilers. A total of 150 broiler chicks were grouped into 6 groups each of 25 chicks. Group one was kept as a control group, while group two and three were treated with florfenicol and L-carnitine, respectively. Group 4 was pre-treated with L-carnitine for three days before florfenicol administration. Groups five and sex were cotreated with L-carnitine and florfenicol and post-treated with L-carnitine for three days after florfenicol administration, respectively. The biochemical analysis, liver indices, antioxidant profile, and histopathological examination were performed to evaluate its ameliorative effects. Results emphasized that florfenicol induced hepatic toxicity in broilers and L-carnitine can ameliorate its action when its usage preceded the florfenicol or when they were used together which reflected by an enhancement in liver indices, antioxidant profile, and histopathological findings. As far as we know this the first study confirming the ameliorative potency of L-carnitine on florfenicol-induced hepatotoxicity.